Advancement in the cancer treatment - Kartan, Preethi (Burlington, ON, Canada : Delve Publishing, 2021)
Cancer: It is a disease where our body cells loose ability to divide at normal rate, this abnormal growth of cells results formation of lumps or tumours in body. Depending on the stage of the cancer and condition of the patient, treatment for the disease is decided. Treatment is given either to cure the disease or to shrink the tumour size or slow down the growth of disease allowing patient to live a normal life or live symptom free if possible. General treatment options available for treating cancer include: Surgery, Chemotherapy, Radiation therapy, Immunotherapy. In this book, discusses some of the advances made in the field of cancer treatment.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Cancer -- Treatment; Cancer -- Immunotherapy; Neoplasms -- therapy; Cancer -- Traitement; Cancer -- Immunothérapie.; Cancer -- Immunotherapy; Cancer -- Treatment